PENGELOLAAN SARANA PRASARANA PENDIDIKAN RESPONSIF GENDER : STUDI DI IAIN JEMBER - Nur Ittihadatul Ummah (Institute for Research and Community Service, Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, East Java, Indonesia., 2019)
Management of gender responsive educational facilities is an important issue that needs serious attention because the management of gender-responsive infrastructure can provide space to ensure the fulfillment of women's and men's rights based on their specific needs so as to create a sense of security and comfort for each user. IAIN Jember is required to pay attention to the specific needs of men and women so that dominance does not occur, does not cause difficulties for certain sexes in the use of infrastructure. Indicators of gender responsive infrastructure include the provision of separate toilets, child care and nursing rooms, provision of closed ablution places, closed prayer rooms, ideal 17 cm staircase facilities, CCTV and adequate lighting. The management of gender responsive educational facilities is needed to realize gender justice and equality, support reproductive and cultural functions. This research uses a qualitative approach with the type of case study research. The technique of collecting data uses observation, interviews and document study. Data analysis using interactive analysis. The validity of the data used source triangulation and method triangulation. The results showed that: the prayer room for employees tends to be open so there is no privacy, there are wheelchairs for students with disabilities, and there is no separate toilet for male and female employees. Pengelolaan sarana pendidikan responsif gender merupakan isu penting yang perlu mendapat perhatian serius karena pengelolaan prasarana tanggap gender dapat memberikan ruang untuk menjamin pemenuhan hak perempuan dan laki-laki berdasarkan kebutuhan spesifiknya sehingga tercipta rasa aman dan nyaman bagi setiap pengguna. IAIN Jember dituntut untuk memperhatikan kebutuhan khusus laki-laki dan perempuan agar tidak terjadi dominasi, tidak menyulitkan jenis kelamin tertentu dalam penggunaan infrastruktur. Indikator infrastruktur responsif gender antara lain penyediaan toilet terpisah, ruang penitipan anak dan menyusui, penyediaan tempat wudhu tertutup, mushola tertutup, fasilitas tangga ideal 17 cm, CCTV dan penerangan yang memadai. Pengelolaan fasilitas pendidikan responsif gender diperlukan untuk mewujudkan keadilan dan kesetaraan gender, mendukung fungsi reproduksi dan budaya. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data menggunakan observasi, wawancara dan studi dokumen. Analisis data menggunakan analisis interaktif. Validitas data menggunakan triangulasi sumber dan metode triangulasi. Hasil penelitian menunjukkan bahwa : mushollah untuk karyawan cenderung terbuka sehingga tidak ada privasi, terdapat kursi roda bagi mahasiswa difabel. Kursi roda ini berada di poli klinik kampus, dan tidak ada pemisahan toilet bagi karyawan laki-laki dan perempuan.